Energy Efficiency Using Particle Swarm Optimization with Adhoc on Demand Distance Vector Routing Protocol over Manet (International Journal of Emerging Trends in Science and Technology, 2017)
Mobile Ad-hoc network (MANET) is a collaboration of portable nodes as well as some computingdevices which can be placed arbitrarily anywhere in the network to perform a particular task such as datatransmission and message passing for various applications. The nodes can transmit data in a particularrange and the nodes are capable of changing their location frequently. In previous research, the energyconsumption is main issue and hence the overall routing performance is reduced significantly. Toovercome the abovementioned issue, in this research, Particle Swarm Optimization-Adhoc On DemandDistance Vector (PSO-AODV) routing protocol is proposed. In this research, the Cluster Head (CH) isselected using PSO algorithm based on the best objective function values. The CH node has capability ofrapid packet delivery ratio and better lower energy consumption. The PSO algorithm is used to select theoptimal node and increases effective routing procedure. The routing process is done by using AODVprotocol in this research. This is used to provide efficient path discovery and provides fast packettransmission and response. Thus the proposed PSO-AODV scheme provides superior performance ratherthan the existing approaches. The result concludes that the proposed PSO-AODV approach has lowerenergy consumption, lower end to end delay, higher packet delivery ratio and higher network lifetimethan the existing approaches.